Psychometric Properties of the Bright Personality Traits Scale in Iranian Students - Ali Ghaemi; Yousef Kheiri; Ali Reza Shafiee-Kandjani; Marzieh Jabbarian; Behzad Shalchi (Taṣvīr-i salāmat)
Background. Bright personality traits are defined as a prosocial personality characteristic that includes altruism, forgiveness, and gratitude. This study investigates the psychometric properties of the Bright Traits Scale. Methods. This descriptive study employed factor analysis, with the statistical population comprising all students at Zanjan University during the 2021-2022 academic year. The research sample was selected using random cluster sampling, consisting of 225 participants for exploratory factor analysis, 225 for confirmatory factor analysis, and 40 for retest reliability. The study utilized the Bright Personality Traits Scale (Gouveia et al., 2021) and the Dark Personality Traits Scale (Johnson and Webster, 2010). Initially, face validity was assessed through expert opinions, followed by reliability evaluation using Cronbach’s alpha and test-retest methods. Exploratory factor analysis was then conducted to discover the underlying structure, and confirmatory factor analysis was performed to assess model fit. Finally, discriminant validity was measured using Pearson’s correlation coefficient. Statistical analyses were carried out using SPSS 25 and AMOS 24. Results. After minor revisions to the scale items, the scale demonstrated favorable face validity. Cronbach's alpha and retest coefficients for all subscales exceeded 0.7, indicating acceptable reliability. Exploratory factor analysis identified three factors—altruism, forgiveness, and gratitude—which collectively explained 51.86% of the variance in scores. Confirmatory factor analysis confirmed a significant relationship between observed variables and latent constructs, indicating that the three-factor structure of the scale had a good fit within the sample (χ²/df = 2.42, GFI = 0.92, AGFI = 0.90, IFI = 0.93, TLI = 0.92, CFI = 0.93, RMSEA = 0.056). Discriminant validity indicated an inverse and relatively strong relationship between bright personality traits and dark personality traits (r = -0.66). Conclusion. The Bright Personality Traits Scale demonstrates satisfactory validity and reliability among students, making it a reliable tool for future research.